2009
DOI: 10.1016/s0929-6646(09)60096-6
|View full text |Cite
|
Sign up to set email alerts
|

Roles of State and Trait Anxiety in Physical Activity Participation for Adults with Anxiety Disorders

Abstract: State anxiety demonstrated greater power than trait anxiety in its relationship with physical activity. These findings suggest that clinical mental health professionals should consider state anxiety when encouraging Taiwanese adults with anxiety disorders to engage in physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…This suggests that other factors might play a role. Previous research in Taiwan indicated that in young children with anxiety, physical activity participation is significantly correlated with perceived physical benefits, higher levels of self-efficacy, more social support, and less reported barriers (Ma et al, 2009). These are consistent with evidence for healthy individuals and may be important factors that were not measured in our study but are key factors to increase physical activity among those with anxiety.…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that other factors might play a role. Previous research in Taiwan indicated that in young children with anxiety, physical activity participation is significantly correlated with perceived physical benefits, higher levels of self-efficacy, more social support, and less reported barriers (Ma et al, 2009). These are consistent with evidence for healthy individuals and may be important factors that were not measured in our study but are key factors to increase physical activity among those with anxiety.…”
Section: Discussionsupporting
confidence: 90%
“…Several cross-sectional studies have identified self-efficacy (810), social support (911), perceived benefits (9, 12), and intentions (8) to be consistent, modifiable theory-based PA correlates among persons with severe mental illness (SMI) such as schizophrenia, major depression, and bipolar disorder. While a correlational relationship suggests an association exists between two factors, it does not imply causality.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety disorder is one of the most prevalent forms of psychological distress (American Psychiatric Association 2000). The number of Taiwanese outpatients with anxiety disorders has also increased in the past decade (Ma et al . 2009).…”
Section: Introductionmentioning
confidence: 99%
“…disorders has also increased in the past decade (Ma et al 2009). In research and clinical interventions for these patients, the main standard for evaluating outcomes is reducing anxiety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation